Effects of Delayed Harvest and Additives on Fermentation Quality and Bacterial Community of Corn Stalk Silage - Guo, Linna; Lu, Yongxiang; Li, Ping; Chen, Liangyin; Gou, Wenlong; Zhang, Changbin (Frontiers in Microbiology, 2021)
This study aimed to investigate the effects of delayed harvest and additives on the fermentation quality and bacterial community of corn stalk silage in South China. The corn stalks after ear harvest at the 0 day (D0), 7 days (D7) and 15 days (D15) were used to produce small-bale silages. The silages at each harvest time were treated without (control, CK) or with Lactobacillus plantarum (LP) and sodium benzoate (BF). The results showed that delayed harvest increased pH and acetic acid content and reduced lactic acid content in corn stalk silage (P<0.05). Compared with CK, the additives decreased the contents of butyric acid and ammonia nitrogen (NH3-N) (P<0.05). The silage treated with LP increased the content of lactic acid and decreased pH (P<0.05); the silage treated with BF decreased counts of coliform bacteria and yeasts and increased residual water soluble carbohydrates (WSC) content (P<0.05). Single Molecule, Real-Time sequencing (SMRT) revealed that the abundance of Lactobacillus plantarum increased, while the abundance of Lactobacillus brevis and Lactobacillus ginsenosidimutans decreased with the delayed harvest. Additives influenced the bacterial community structure of corn stalk silage, revealed by enhanced bacterial diversity on D0 and reduced on D7 (P<0.05). Our research indicated that delayed harvest could exert a positive effect on acetic acid production, and additives could inhibit the butyric acid fermentation and protein degradation of corn stalk silage by shifting bacterial community composition.